Partisipasi Masyarakat Dalam Pembangunan Infrastruktur di Desa Kila Kecamatan Aimere - Maria Yohana Wio; Hendrik Toda; Aspri Budi Oktavianto; Umbu T. W. Pariangu (Student Research Journal, 2026)
Community participation is an important factor in supporting the success of village infrastructure development. This study aims to analyze community participation in infrastructure development in Kila Village, Aimere District, Ngada Regency. The research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation involving village officials, community leaders, and local residents. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that community participation in infrastructure development has not been evenly distributed across all stages of development. Participation at the planning stage remains relatively low due to limited community involvement in development planning meetings. In contrast, participation during the implementation stage is relatively high, particularly through mutual cooperation activities and labor contributions. At the utilization stage, the community has benefited from the infrastructure development; however, awareness regarding the maintenance and preservation of development outcomes remains low. Factors supporting community participation include public awareness, the culture of mutual cooperation, and support from the village government. Meanwhile, inhibiting factors include limited time, educational background, low community initiative, and inadequate socialization. The study concludes that community participation in infrastructure development in Kila Village needs to be strengthened, particularly at the planning and maintenance stages, in order to achieve more participatory and sustainable village development.